Kontribusi-Dimensional Perguruan Tinggi Swasta Terhadap Bangunan Sosial dan Budaya Masyarakat Madura (Studi atas Kiprah Perguruan Tinggi Swasta di Kabupaten Sumenep Madura) - Rahem, Zaitur (Jurnal Penjaminan Mutu, 2017)
Higher Education (PT) is a central science, and barns civilized culture. In Indonesia, there are typologies PT accordance with struktualis power limit. Namely, PT who are under the authority Kemendikbud and Kemenag. Although different house, but the same substance. All elements have the same commitment membersarkan education premises. Under the supervision of Religious Affairs, PT spread across all regions of the country. At the level of management, there are private and public PT. PT Private independently but administratively connected with the government. PT-PT private during this, the procedure of governance and there are already established there are still 'semraut'. PT-managed properly been able to provide a study room and an incredible inspiration to mental development and the custom of society. In Madura, Sumenep regency especially the private PT has a strategic role in human development and the environment. It happens, because in the life of PT contained Tridharma college mission. Insan PT determined to always be the transformation of knowledge, devotion, and conduct research for the common good.Studies in this paper will reveal the scientific facts tentrang college of contributions and dedication in the area of Madura. The method in this study using a qualitative ethnographic approach, the technique of participant observation data collection, data sources through snowball sampling. The results of this study reveal the facts, Madura College in the Region is able to provide the benefits of environmental and human dimensional. Starting from the texture of culture, civilization advanced and new, as well as the human characters more educated.